DEKONSENTRASI DAN DESENTRALISASI DALAM DISKURSUS NEGARA KESATUAN DAN NEGARA FEDERAL - Tri Widodo W. Utomo2 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
There is no general agreement among scholars on the degree of decentralization in a certain country. There is also disagreement whether unitary states tend to be more centralized while federal states are likely more decentralized. Yet, comparing unitary and federal states in implementing decentralization and its variants is always interesting. This paper elaborates the nature of unitary and federal states, then explores some practical aspects on the implementation of decentralization in each type of state.